Moving Target Tracking and Imaging Through Scattering Media via Speckle-Difference-Combined Bispectrum Analysis - Yingbo Wang; Jie Cao; Chengqiang Xu; Yang Cheng; Xuemin Cheng; Qun Hao (IEEE Photonics Journal, 2019)
Target tracking and imaging through scattering media are challenges that must be overcome for important applications in various fields. The fundamental problem is the randomly diffused light in scattering media that prevents the formation of diffraction-limited images. In recent years, speckle correlation has emerged as a powerful approach for restoring targets through scattering media and tracking targets with high scattering. However, this method fails to achieve high-accuracy target tracking in multidimensional motion. Furthermore, retrieving the deterministic phase of a target in a low-resolution speckle pattern is limited. Here, a method based on speckle-difference-combined bispectrum analysis (SDCBA) is presented to simultaneously track and image targets. The proposed SDCBA requires no high-resolution pattern, randomly assigned initial values, nor numerous iterations. The target is tracked simultaneously in multidimension by using speckle difference autocorrelation and restored with the deterministic phase via bispectrum analysis of the low-resolution speckle pattern. This work carries out simulations and experiments to demonstrate simultaneous multidimensional target tracking and imaging in low-resolution speckle pattern through scattering media via the SDCBA. This work will benefit various fields, including biomedical applications, materials science, and military security.